The Magnetic Receptor of Monascus ruber M7: Gene Clone and Its Heterologous Expression in Escherichia coli - Zhou, Hongyi; Yang, Shuyan; Chen, Fusheng (Frontiers in Microbiology, 2020)
It is well known that many organisms can sense the magnetic field (MF) including the geomagnetic field, but how to feel MF has not been well-known yet. Recently, a new study has claimed that a biological compass, namely a complex of the magnetic receptor (MagR) and blue light (BL) receptor (cryptochrome), has been found in Homo sapiens, Drosophila melanogaster and Danaus plexippus, which may bring some new ideas to explore the mechanism. Monascus spp. are edible filamentous fungi that can produce abundant beneficial secondary metabolites and have been using to produce food additives nearly 2000 years in the world, especially in China. In this work, firstly we treated M. ruber M7 by BL (500 lux，465-467 nm), MF (5, 10, 30 mT) and combination of MF and BL (MF-BL), respectively. The results revealed that compared with the control (CK, neither BL nor MF), the MF alone had no evidently effect on the growth and morphological characteristics of the M7, but BL makes the colony diameter only 66.7% of CK and inhibits the formation of cleistothecium. Under MF-BL conditions, the colony diameter was still 66.7% of CK, but the colonies grow vertically and restore the ability to produce cleistothecium. Then we have found that magR gene widely exists in the genomes of animals, plants and microorganisms, and we have also discovered a magR gene in the M7 genome, hereinafter referred to mr-magR. Finally, the full-length cDNA of mr-magR was successfully cloned and expressed in Escherichia coli BL21 (DE3), and the Mr-MagR protein was purified by a Ni+-NTA column and identified by Western blot. These results have laid a foundation for further investigation on the relationship between Mr-MagR and BL receptors that may exist in M7. According to our knowledge and the literature search, it is the first report of the magR gene in filamentous fungi.